Collaborative In-Service Training: An Effort to Help EYL Teachers Improve Their Teaching Skills - Oktora, Anggraeni Rety; Nur’Aini, Siti; Wiyaka, Wiyaka (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The Decree of The Ministry of Education and Culture No 060/U/1993 allows the introduction of English in the primary school as a local content subject. Educators have debated for years about the teaching of English to young learners in Indonesia. It is recommended that students start learning English at fourth grade although in fact, many schools start earlier, even as early as in the kindergarten. Talking about the implementation of the EYL programmes, it is inevitable to recognize that many factors have affected the implementation. Several studies have been conducted by the instructors and teacher trainers. It was discovered that most teachers did not have sufficient knowledge of English, made common linguistic mistakes, did not know how to teach young learners and some other weaknesses. The writer made use of the research findings to conduct in-service trainings, especially for EYL teachers without any English education background. Based on the teacher questionnaires, this collaborative in-service training pinpoints specific areas: practical teaching techniques focusing on story-telling, playing games, using action songs, and making inexpensive media for classroom techniques. Why collaborative in service training? Conducting in-service trainings for EYL teachers takes time, energy, and money. In this case Suyanto and her teams have applied a strategy involving the teacher trainers or instructors, the EYL teachers, the local Ministry of Education, and the important community members (hotel manager, the wealthy and local sponsors). Proposals with clearly stated objectives (helping local teachers improve their skills and increase the quality of primary school education) have been accepted and positively supported by the local government, local ministry of education and local society.